2021
DOI: 10.1002/qj.4131
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of moisture flux anomalies indicating central European extreme precipitation events

Abstract: Forecasting heavy precipitation has an important role in mitigating floods and associated hazards, but it remains one of the main challenges in operational meteorology. Our previous study confirmed the close connection between large‐scale extreme precipitation events and anomalous moisture fluxes in central Europe. In this study, we introduce a variable accounting for the accumulated ascending moisture flux, which could potentially support extreme precipitation event forecasts. The variable reflects the total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The reason for this is that models are able to predict large-scale circulation much better than smaller-scale phenomena, and taking into account that moisture transport is related to larger-scale circulation, it can be assumed that its predictability will be better than in the case of precipitation, which is more conditioned to more complex and smaller-scale atmospheric processes 48 . For medium-range (submonthly) time scales, Lavers et al 49 demonstrated that integrated vertical moisture transport (a measure of moisture transport) was more predictable than precipitation in northwestern Europe and the western US, and the results obtained by Gvoždíková and Müller 50 for Central Europe are in line with it. For seasonal time scales, Wang and Yuan 51 for China's Yangtze River basin and Gao et al 52 for the Northern Hemisphere also show the greater predictability of moisture transport.…”
Section: Potential Of Moisture Transport In Drought Predictabilitymentioning
confidence: 85%
“…The reason for this is that models are able to predict large-scale circulation much better than smaller-scale phenomena, and taking into account that moisture transport is related to larger-scale circulation, it can be assumed that its predictability will be better than in the case of precipitation, which is more conditioned to more complex and smaller-scale atmospheric processes 48 . For medium-range (submonthly) time scales, Lavers et al 49 demonstrated that integrated vertical moisture transport (a measure of moisture transport) was more predictable than precipitation in northwestern Europe and the western US, and the results obtained by Gvoždíková and Müller 50 for Central Europe are in line with it. For seasonal time scales, Wang and Yuan 51 for China's Yangtze River basin and Gao et al 52 for the Northern Hemisphere also show the greater predictability of moisture transport.…”
Section: Potential Of Moisture Transport In Drought Predictabilitymentioning
confidence: 85%
“…Water vapor is mainly concentrated in the lower atmosphere. There are many meteorological methods for estimating vertical airflow, but all of them do not correspond to the location, intensity, and timing of extreme precipitation [56]. The strongest convergence of atmospheric horizontal airflows is in the upper troposphere, but there is a lack of water vapor aloft.…”
Section: Extratropical Cyclonesmentioning
confidence: 99%
“…Ongoing research investigates the option of using predictors other than direct model precipitation output to inform about precipitation state and EPEs. Such studies, for example, make use of relative humidity (Reggiani & Weerts, 2008), atmospheric rivers (in the United States of America: Lavers, Waliser, et al, 2016 and Europe: Lavers et al, 2018; Lavers, Pappenberger, et al, 2016), or large‐scale atmospheric variability (over the United Kingdom: D. Richardson, Fowler, et al, 2020; D. Richardson, Neal, et al, 2020, India: Neal et al, 2020, Europe: Gvoždíková & Müller, 2021; Krouma et al, 2022, or southeast Asia: Howard et al, 2022). Connections between sea surface temperature and continental precipitation have also been studied by Rieger et al (2021).…”
Section: Introductionmentioning
confidence: 99%